Training of small-scale dairy women vendors on use of solar-powered mini-pasteurizer for safer milk in Nairobi - Sharma, Garima; Alonso, Silvia; Mutua, Florence K.; Kibet, George (International Livestock Research Institute, 2025)
The International Livestock Research Institute and the Kenya Dairy Board trained small-scale women milk vendors on how to use an innovative mini-pasteurizer to ensure milk safety.